A New Cosmology Based on the Unified Complex Systems Theory (UCST) - Cui, Weicheng (European Journal of Applied Sciences, 2026)
This paper presents a novel, self‑consistent cosmological framework rooted in Unified Complex System Theory (UCST), clarifying the fundamental distinction between the “Universe” and the “World” to resolve foundational flaws in modern cosmology. The Universe is defined as an infinite, eternal, philosophically transcendent spacetime totality beyond empirical observation. The World, by contrast, is the finite, observable spacetime domain that forms the proper subject of scientific cosmology, redefined here as the mathematical and experimental study of the World’s cyclic evolution—formation, persistence, decay, and regeneration—under strict mass, momentum, and energy conservation. Celestial bodies, particles, and atoms are categorized as “living agents” due to autonomous motion and adaptive responses, defined by dynamics rather than biological traits. Their motion is governed by conventional passive forces (gravity, electromagnetism, air damping) and intrinsic adaptive active forces, which stabilize orbits via natural energy compensation, removing the need for dark matter and dark energy. Supported by mathematical logic and qualitative agreement with observational phenomena, the proposed framework is shown to outperform the ΛCDM model in coherence, parsimony, predictive capability and falsifiability. Quantitative evaluation using empirical measurements is therefore necessitated. Where quantitative validity is established, key ΛCDM anomalies—including the Hubble tension, singularity, horizon, flatness, cosmological constant, dark sector puzzles and cosmic age discrepancies—may be resolved. Rigorous axiomatics and testable predictions are provided for independent validation, enabling this construct to be regarded as a coherent alternative paradigm in cosmology.